Wage dispersion and firm productivity in different working environments - Benoît Mahy; François Rycx; Mélanie Volral (Institute for the Study of Labor (IZA), 2009)
This paper investigates the impact of wage dispersion on firm productivity in different working environments. More precisely, it examines the interaction with: i) the skills of the workforce, using a more appropriate indicator than the standard distinction between white- and blue collar workers, and ii) the uncertainty of the firm economic environment, which has, to our knowledge, never been explored on an empirical basis. Using detailed LEED for Belgium, we find a hump-shaped relationship between (conditional) wage dispersion and firm productivity. This result suggests that up to (beyond) a certain level of wage dispersion, the incentive effects of tournaments dominate (are dominated by) fairness considerations. Findings also show that the intensity of the relationship is stronger for highly skilled workers and in more stable environments. This might be explained by the fact that monitoring costs and production-effort elasticity are greater for highly skilled workers and that in the presence of high uncertainty workers have less control over their effort-output relation and associate higher uncertainty with more unfair environments.
urn:nbn:de:101:1-20090323134
Keywords: J31; J24; M52; 330; Wage dispersion; labour productivity; working environments; personnel economics; linked employer-employee data; Lohnstruktur; Produktivität; Arbeitsbedingungen; Extensives Spiel; Humankapital; Leistungsmotivation; Gerechtigkeit; Risiko; Belgien